Pembelajaran Kooperatif Berbantuan Media Video Pembelajaran pada Materi Mari Berhemat Energi Listrik Kelas IV SD - Setiawan, Heri; Fatimah, Siti (Educational Consultant & Counseling Career (EC3) Mataram, 2023)
This writing aims to describe the learning process that applies the cooperative learning model assisted by learning videos on the material of how to save electrical energy as well as attitudes of cooperation and student learning outcomes. The learning model used in this lesson is a cooperative learning model assisted by learning video media on the material let's save energy for class IV Elementary School. The learning process takes place referring to the six steps of the cooperative learning model, namely (1) present goal and set; (2) present information); (3) organize students into learning; (4) assist team work and study; (5) test on materials; and (6) provide recognition.